WhatsApp as a Tool in Blended Learning in Dental Education - Gunasekaran Lalithambigai; Khair Al Moutassem B; Shetty Raghavendra; Shetty Naresh (Wolters Kluwer Medknow Publications, 2024)
Background and ObjectiveDental education is unique, with clinical/practical learning much different from other professionals. In dentistry, students are exposed much earlier in their curriculum to patients, performing procedures under direct/indirect supervision. Hence, the present review attempted to assess the standing position of dentistry in blended learning worldwide. Materials and MethodsE-learning modality was at its primitive stage as food for thought among educational task force committees, with only a handful of developed and developing countries equipped with it. During this pandemic, "WhatsApp" became a savior, as it was a widely used educational device among dental teachers and students. Furthermore, it was easily applicable in places where there was difficulty in obtaining regular internet bandwidth, especially in remote/rural areas. It is noteworthy that blended learning/e-learning, when complemented with the conventional teaching method, upskill critical thinking and problem-solving capabilities. Blended learning or virtual reality education should be made feasible without disparity, worldwide. Mind training, both students and staff in hybrid e-learning, is the need of the hour not only to keep pace with digitalized dentistry but to prepare the students to face real-world situations. ConclusionThe sustainability of dental education should be rethought by dental schools with "Complimented Digital learning" wherever feasible, not only to cope with current trends but also to face unforeseen future challenges.